2013
DOI: 10.1371/journal.pone.0072821
|View full text |Cite
|
Sign up to set email alerts
|

Role of the N-Terminal Seven Residues of Surfactant Protein B (SP-B)

Abstract: Breathing is enabled by lung surfactant, a mixture of proteins and lipids that forms a surface-active layer and reduces surface tension at the air-water interface in lungs. Surfactant protein B (SP-B) is an essential component of lung surfactant. In this study we probe the mechanism underlying the important functional contributions made by the N-terminal 7 residues of SP-B, a region sometimes called the “insertion sequence”. These studies employed a construct of SP-B, SP-B (1–25,63–78), also called Super Mini-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The SP-B analogue of CHF5633 lacks the first 7 aminoacids with respect to full length, wt SP-B. The 7 residues at the N-terminus constitute the membrane insertion sequence, which is reported to cause a dramatic increase in the acyl chain disorder in the center of the bilayer [ 44 ]. The Trp residue of SP-B analogue of CHF5633 reports the same polarity as Trp of peptides presenting the 7 amino acids insertion sequence, suggesting an unaltered location and a maintained capacity of anchoring on the membrane surface.…”
Section: Resultsmentioning
confidence: 99%
“…The SP-B analogue of CHF5633 lacks the first 7 aminoacids with respect to full length, wt SP-B. The 7 residues at the N-terminus constitute the membrane insertion sequence, which is reported to cause a dramatic increase in the acyl chain disorder in the center of the bilayer [ 44 ]. The Trp residue of SP-B analogue of CHF5633 reports the same polarity as Trp of peptides presenting the 7 amino acids insertion sequence, suggesting an unaltered location and a maintained capacity of anchoring on the membrane surface.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of structural features of SP-B have previously been suggested to contribute to SP-B-mediated lipid structural transitions, and will be considered in turn in the light of this work’s simulations of SP-B dimers. Firstly, the N-terminal seven residues of SP-B, with sequence FPIPLPY, have been termed the “insertion sequence” and have been proposed to be important in helping SP-B insert into the air/lipid interface [34,35]. In all simulations, with the exception of the CO2 system, this region of SP-B was observed to localize tightly to the polar/apolar interface of the lipids.…”
Section: Discussionmentioning
confidence: 99%
“…It is even possible that SP-B’s topology changes during the respiratory cycle (i.e., as the air/water surface is compressed upon expiration and expands upon inspiration), or that the SP-B topology is different in different LS lipid structures. One additional structural feature to note is the seven N-terminal residues of SP-B, with sequence FPIPLPY, which have been termed the “insertion sequence” and have been proposed to help SP-B insert into the lipid monolayer at the air/water interface [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Adding these seven residues to Mini-B, resulting in an analogue referred to as Super Mini-B increases the surfactant activity in vitro and in vivo [182,183]. The CD spectra of the N-terminal heptapeptide alone confirmed that it does not form an a-helical structure, and Super Mini-B shows similar contents of an a-helical structure such as Mini-B [181]. Super Mini-B also appears to be a more stable dimer at submicellar SDS concentrations than Mini-B, thereby mimicking better the native SP-B.…”
Section: Design Of Sp-b Analoguesmentioning
confidence: 97%
“…b) . Further studies have suggested an important role of the N‐terminal hydrophobic seven‐residue segment of SP‐B (FPIPLPY, Table ), that are not included in Mini‐B . The three Pro in this motif probably efficiently prevent the formation of an α‐helix and the high hydrophobicity could promote interactions with surfactant phospholipid membranes.…”
Section: Design Of Sp‐b Analoguesmentioning
confidence: 99%